Secondary Fast Breakdown in Narrow Bipolar Events. Issue 7 (5th April 2022) - Li, Dongshuai; Luque, Alejandro; Gordillo‐Vázquez, F. J.; Silva, Caitano da; Krehbiel, Paul R.; Rachidi, Farhad; Rubinstein, Marcos
Abstract: The physical mechanism of Narrow bipolar events (NBEs) has been studied for decades but it still holds many mysteries. Recent observations indicate that the fast breakdown discharges that produce NBEs sometimes contain a secondary fast breakdown that propagates back in the opposite direction but this has not been fully addressed so far in electromagnetic models. In this study, we investigate fast breakdown using different approaches that employ a Modified Transmission Line with Exponential decay (MTLE) model and propose a new model, named "rebounding MTLE model, " which reproduces the secondary fast breakdown current in NBEs. The model provides new insights into the physics of the fast breakdown mechanism. Plain Language Summary: Narrow bipolar events (NBEs) are intense, bipolar‐shaped radio signals emitted from thunderstorms. Because their origin is still poorly understood, they have attracted a great deal of interest in the atmospheric electricity community. Recently, it has been found that NBEs are likely produced by extensive electrical discharges named fast breakdown which are likely composed of millions of thin filaments called streamers. In this study, we propose a model for the fast breakdown current in which we consider that the primary streamer discharge triggers a second breakdown wave, also composed of streamers and propagating in the opposite direction. Our model unveils features of the fast breakdown that can play a key role in our understanding of this phenomenon. Key Points: The primary streamers of fast breakdown in Narrow Bipolar Events trigger a secondary fast breakdown of the opposite polarity Secondary fast breakdown is analyzed by using a new proposed model The current pulse of Narrow Bipolar Events is not extinguished at the end of the discharge but instead reverses its direction